Work-care balance among parent-workers in Malaysian urban organizations: role and quality of children's daycare centers - Abd. Rokis, Rohaiza (Center for Promoting Ideas (CPI), USA, 2014)
Many modern parents-workers today contribute to the survival and maintenance of their households. However, work-life-balance is always their perennial issue. Indisputably, the domestic and financial demands have an effect on their lives. Preceding literature in Malaysia discussed the effects of parenting styles on the development of children. However, the attitudes of parents-workers on parenting and childcaring demonstrate a clear gap towards children's development and parents-workers' well-being. It is therefore pertinent here to explore the attitudes of the parents-workers in handling the children's daycare centers issues. The research is a survey project using questionnaires onto 558 parents-workers who working different constituencies in Malaysia. It is concluded that parents-workers are inclined to have a convenient attitude in sending their children to children's daycare centers as long as they are cared while they are out at work. The result is distressing. The research consequently recommends establish integrated children's daycare centers within the community.